2021
DOI: 10.1093/clinchem/hvaa323
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Multiplex Digital Droplet RT-PCR as a Diagnostic Tool for SARS-CoV-2 Detection in Nasopharyngeal Swabs and Saliva Samples

Abstract: Background Reverse transcription-quantitative PCR on nasopharyngeal swabs is currently the reference COVID-19 diagnosis method but exhibits imperfect sensitivity. Methods We developed a multiplex reverse transcription-digital droplet PCR (RT-ddPCR) assay, targeting six SARS-CoV-2 genomic regions, and evaluated it on nasopharyngeal swabs and saliva samples collected from 130 COVID-19 positive or negative ambulatory individuals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 24 publications
1
36
0
3
Order By: Relevance
“…It must be considered that the presence of SARS-CoV-2 RNA in saliva and negative results in nasopharyngeal samples analyzed by RT-PCR cannot be classified as false positive, but a misclassification of nasopharyngeal samples. This pivotal view is well-documented in a previous study that showed 71% of matched detection of SARS-CoV-2 RNA in saliva and nasopharyngeal swabs, 21% only in saliva, and 8% only in nasopharyngeal swabs ( 52 ). It can be related with the limitations in nasopharyngeal swab procedure and/or with low produced nasopharyngeal mucous secretion in COVID-19 patients.…”
Section: Future Directionssupporting
confidence: 63%
“…It must be considered that the presence of SARS-CoV-2 RNA in saliva and negative results in nasopharyngeal samples analyzed by RT-PCR cannot be classified as false positive, but a misclassification of nasopharyngeal samples. This pivotal view is well-documented in a previous study that showed 71% of matched detection of SARS-CoV-2 RNA in saliva and nasopharyngeal swabs, 21% only in saliva, and 8% only in nasopharyngeal swabs ( 52 ). It can be related with the limitations in nasopharyngeal swab procedure and/or with low produced nasopharyngeal mucous secretion in COVID-19 patients.…”
Section: Future Directionssupporting
confidence: 63%
“…Similarly, Suo et al reported that 26 patients deemed negative by RT-PCR (out of 77 patients) were detected as positive by ddPCR 27 . In another study, multiplex ddPCR was used to test saliva and NP samples from 130 individuals with COVID-19 symptoms, and ddPCR was found to be superior to RT-PCR in determining positive cases 28 . Results published by several recent studies also support the use of ddPCR as a sensitive method for SARS-CoV-2 detection and quantification 29 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental setups, such as specimen type and primer–probe sets used, can impact test accuracy, which ranges from 47% to 100% in various PCR studies. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 LAMP also differs in reported accuracy (61–100%) depending on the viral content of the sample and reference test used. 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 This large variation in reported accuracies of PCR and LAMP is due to the absence of a standardised measure for evaluating diagnostic test accuracy and the experimental setups that vary across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many studies have assessed the accuracy of the PCR and LAMP methods separately, their experimental setups differ greatly, leading to test result variations and disagreement in conclusions on which nucleic acid test is the most accurate. 6 , 7 , 8 , 9 , 10 , 11 , 13 , 14 , 15 , 17 , 20 , 21 , 24 , 25 , 26 , 28 , 29 , 35 , 36 , 37 , 38 , 39 For example, of the three studies that previously reviewed diagnostic tests, including chest CT, antigen tests, isothermal amplification, and qPCR, a small number of trials and limited subgroups were analysed with large experimental variations. 4 , 40 , 41 …”
Section: Introductionmentioning
confidence: 99%